The role of scoring in formative assessment of second language writing - Sookyung Cho; Chanho Park (Penerbit Universiti Kebangsaan Malaysia, 2014)
This study examines how scoring with feedback in formative assessment affects learning in an English as a foreign language (EFL) writing classroom. Two EFL writing classes were compared: in one class, teacher feedback was given to students on initial drafts, and scores were given only at the end of the semester; in the second class, teacher feedback and scores were given to students on each draft throughout the semester. This study adopted a mixed-methods approach, including a statistical analysis to explore whether teacher feedback accompanied by scoring makes a difference in student writing, and observation, and interviews of focal students to examine how feedback with scores affects students’ perceptions and attitudes towards writing. The results reveal that the scoring class wrote more accurately than the non-scoring class and that the focal students in the scoring class were not only more aware of both their own and their classmates’ performances, but that they also made efforts to emulate the students they considered effective writers. This study implies that scoring can fortify the effects of feedback by motivating high achieving students to do their best in their writing assignments.